The Impact of Strategic Agility on Building the Intelligent Organization: A Field Study in Private Hospitals in Ibb City - Majed Kassem Alsyani; Madihah Hussein Mohammed (University of Science and Technology, Sana’a, Yemen, 2023)
The study aimed at identifying the impact of strategic agility on building the intelligent organization through the dimensions of strategic agility (strategic sensitivity, leadership unit, resource fluidity, decision –making agility, strategic vision, and response speed) and its role in building the intelligent organization in private hospitals. A comprehensive survey method was used to collect data, involving the administrative leaders in private hospitals in Ibb City. A total of 130 questionnaires were distributed to administrative leaders (general managers, department managers, department Head and their deputies). The study revealed numerous significant findings, including a statistically significant impact of strategic agility on building the intelligent organization. The study also indicated a significant impact of the dimensions of strategic agility (strategic sensitivity, resource fluidity, decision-making agility and response speed) on constructing the intelligent organization. However, there is no significant impact of the dimensions of strategic agility (leadership unit and strategic vision) on building the intelligent organization. The study recommended various suggestions, including the necessity for organizations to adopt the strategic agility approach, focus on resources, and establish a clear strategic vision to facilitate rapid interaction with the surrounding environment. Furthermore, it emphasizes the importance of involving the employees in developing a strategic plan that aligns with their mental and physical skills and orientations.